RELIGIOUS FACTORS IN GEORGIAN POLITICS (THE 2008 GENERAL ELECTIONS) - DUNDUA, Salome (CENTRAL ASIA AND THE CAUCASUS, 2010)
Georgia has always been, and remains, part of the Christian Orthodox world, which means that the use of religion as a political instrument should not shock anyone.Indeed, in the context of the struggling economy, the civil institutions are unable to inculcate democratic consciousness, without which a single civil expanse is impossible. The Church, sporadically aided by political actors, has shouldered the responsibility for performing at least some of the functions of these institutions.In recent years, the Church’s stronger role in the country’s political, social, and spiritual life has been reflected in the results of the elections at the local and national levels. The religious factor is rapidly gathering political hues, a fact clearly demonstrated by the presidential and parliamentary elections of 2008.Below I shall rely on the returns of the March 2008 sociological poll to identify the extent to which the religious factors affected the election results and the role of the Georgian Orthodox Church in the country’s social life. My conclusions are based on scrupulous analysis of the poll’s results.